1984
DOI: 10.1136/bmj.288.6417.597
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of osteoporosis in women with fracture of the femoral neck.

Abstract: A prospective study of fractures of the femoral neck was conducted over 12 months in order to ascertain the relevance of generalised osteoporosis as determined by metacarpal morphometry. A series of some 200 women sustaining a fracture of the femoral neck after minor trauma had bone mass measurements similar to those of a control population of normal women, and 16% were not osteoporotic. A history of previous fractures was documented in one third of the women, but this was unrelated to the presence or severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 22 publications
(4 reference statements)
2
24
0
4
Order By: Relevance
“…and are more prone than cervical fractures to occur in an osteoporotic population. This factor was supported by a prospective study in women (Aitken 1984). Moreover, in men the C/T ratio did not decrease with age; it was close to 1 before 50 years whereas, after 70 years the incidence of cervical fractures exceeded that of the trochanteric.…”
Section: Agesupporting
confidence: 64%
“…and are more prone than cervical fractures to occur in an osteoporotic population. This factor was supported by a prospective study in women (Aitken 1984). Moreover, in men the C/T ratio did not decrease with age; it was close to 1 before 50 years whereas, after 70 years the incidence of cervical fractures exceeded that of the trochanteric.…”
Section: Agesupporting
confidence: 64%
“…Falchet al (1985) and Zetterberg et al (1984) also found adecreasing ratio cervical to trochanteric fractures with increasing age. This might be an indication that trochanteric fractures are due more to bone fragility owing to age than the cervical ones (Aitken 1984).…”
Section: Discussionmentioning
confidence: 99%
“…1 Intraoperative deaths (cardiac arrest) during hip arthroplasty occur infrequently and have been associated with bone cement (BCIS). 7,8 Patients with severe underlying cardiovascular In our series, the average operative time was 66.55 min (range 50-90min) and average blood loss 256.33ml (range: 150-450 ml).…”
Section: Discussion:-mentioning
confidence: 99%
“…Fractures of neck of femur are commonly seen in elderly people although all age groups can be affected, but increased predilection is seen in osteoporotic bones (Aitken, 1984).The best treatment for the active and lucid elderly patient with displaced intra-capsular femoral neck fracture is still controversial and has been rightly called "Unsolved Fracture" by Dickson (1953). Due to high energy road traffic accidents the fracture have presented in young patients further complicating the establishment of definitive treatment.…”
Section: Introduction:-mentioning
confidence: 99%